1994
DOI: 10.1007/bf00360548
|View full text |Cite
|
Sign up to set email alerts
|

A novel, conserved gene of the rat that is developmentally regulated in the testis

Abstract: From a rat testis library three overlapping cDNA clones were isolated that represent a novel single-copy gene, designated Tegt. Two transcripts of 2.8 and 1.0 kb were found in each organ tested. The shorter transcript was highly abundant in adult testis. A similar expression pattern was found in the mouse. Analysis of rat RNA from different stages of spermatogenesis indicated that accumulation of the short transcript occurred mainly postmeiotically. The rat Tegt gene maps to Chromosome (Chr) 7, and its mouse h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Another member of this family shares several common features with LFG: the antiapoptotic protein BI-1. The gene encoding for BI-1 was identified in 1994 by Walter et al as a singlecopy gene for which 2 transcripts were found in every organ tested (20). In studies with in vitro translated protein and transiently overexpressed protein, it was shown that BI-1 is localised mainly in the endoplasmatic reticulum (21 (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Another member of this family shares several common features with LFG: the antiapoptotic protein BI-1. The gene encoding for BI-1 was identified in 1994 by Walter et al as a singlecopy gene for which 2 transcripts were found in every organ tested (20). In studies with in vitro translated protein and transiently overexpressed protein, it was shown that BI-1 is localised mainly in the endoplasmatic reticulum (21 (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…BI-1 (Bax inhibitor 1), also known as TEGT (21), was identified as a suppressor of Bax-induced cell death in a yeast-based screen for mammalian cytoprotective proteins (22). BI-1 is an evolutionarily conserved, multitransmembrane protein that resides in the ER in both animal and plant cells (22)(23)(24)(25) and that displays cytoprotective activity when overexpressed in animal or plant cells (23, 26 -31).…”
mentioning
confidence: 99%
“…Alas, it turned out later, that the gene was a pseudogene and that the reading frame was wrong (Manz et al, 1993). In the meantime, a monoclonal antibody directed against a synthetic peptide created in phase with the false reading frame, had already lead to the discovery of a rat gene and its human homolog, both autosomally encoded, with, of course, no trace of homology to the real TSPY, but -what a remarkable coincidence -abundantly expressed in the testis (Walter et al, 1994;Walter et al, 1995).…”
mentioning
confidence: 99%